Penggunaan Media Gambar Seri Untuk Meningkatkan Hasil Belajar Menulis Cerita Pada Siswa Kelas III di SDN-4 Menteng Palangkaraya: The Use of Picture-Series Media to Improve Learning Outcomes of Story Writing for Third-Graders of Primary School at SDN-4 Menteng Palangkaraya - Clara Lunsabiani; Fauziah Bestari; Sulistya Wati (Jurnal Pendidikan Dasar dan Menengah, 2023)
This classroom action research was carried out with the aim of improving Indonesian language learning outcomes in Story Writing material using series of picture media for class IIIc students at SDN-4 Menteng Palangkaraya for the 2022/2023 academic year. To improve Indonesian language learning outcomes for class IIIc students at SDN-4 Menteng Palangkaraya, researchers used the serial-story writing technique. This classroom action research method is carried out in stages (1) planning, (2) action, (3) observation, (4) reflection. The subjects of this research were 29 students of class IIIc, consisting of 16 males and 13 females. The data collection techniques used were tests, observation, interviews and documentation which were then analyzed using descriptive qualitative. The results of the research show that the percentage of completeness of student learning outcomes has increased, before the action was taken 66% were complete with an average class score of 63.6. In cycle I there was an increase of 73% completion with an average grade of 68, in cycle II there was an increase of 90% completion with an average grade of 76. Thus, it can be concluded that the learning outcomes of class IIIc students at SDN-4 Menteng Palangkaraya have increased by using series of picture media in the Indonesian language subject of "Story Writing".